IL-17+ Mast Cell/T Helper Cell Axis in the Early Stages of Acne - Eliasse, Yoan; Leveque, Edouard; Garidou, Lucile; Battut, Louise; McKenzie, Brienne; Nocera, Thérèse; Redoules, Daniel; Espinosa, Eric (Frontiers in Immunology, 2021)
Acne is a multifactorial disease driven by physiological changes occurring during puberty in the pilosebaceous unit (PSU) that leads to sebum overproduction and a dysbiosis involving notably Cutibacterium acnes. These changes in the PSU microenvironment lead to a shift from a homeostatic to an inflammatory state. Indeed, immunohistochemical analyses have revealed that inflammation and lymphocyte infiltration can be detected even in the infraclinical acneic stages, highlighting the importance of the early stages of the disease. In this study, we utilized a robust multi-pronged approach that included flow cytometry, confocal microscopy, and bioinformatics to comprehensively characterize the evolution of the infiltrating and resident immune cell populations in acneic lesions, beginning in the early stages of their development. Using a discovery cohort of 15 patients, we demonstrated that the composition of immune cell infiltrate is highly dynamic in nature, with the relative abundance of different cell types changing significantly as a function of clinical lesion stage. Within the stages examined, we identified a large population of CD69+ CD4+ T cells, several populations of activated antigen presenting cells, and activated mast cells producing IL-17. IL-17+ mast cells were preferentially located in CD4+ T cell rich areas and we showed that activated CD4+ T cells license mast cells to produce IL-17. Our study reveals that mast cells are the main IL-17 producers in the early stage of acne, underlying the importance of targeting the IL-17+ mast cell/T helper cell axis in therapeutic approaches.